Availability of firms' information and their choice of external credit: Evidence from the data of small firms - Wako Watanabe (Osaka University, Institute of Social and Economic Research (ISER), 2004)
The main purpose of this paper is to present the empirical findings derived from the data of small firms that the availability of private and public information on the borrowing firm leads to diverse borrowing patterns among firms. Exploring logit models to characterize the firm's choice of a financial source, we find that firms whose information is poorly recorded, or who are publicly less recognized, are more likely to choose institutional lending over trade credit but as the recorded information becomes more organized and firms become more transparent, they tend to graduate to a greater use of trade credit.
Keywords: C25; G21; G32; 330; availability of information; institutional lending; trade credit; nested logit models; Asymmetrische Information; Informationsversorgung; Bank; Lieferantenkredit; KMU; Logit-Modell